Hubungan Career Decision Making Self-Efficacy terhadap Career Indecision pada Siswa SMK Negeri 3 Padang - Ilahi, Rida Admi; Guspa, Anindra (Lembaga Yasin AlSys, 2024)
This study aims to examine the relationship between Career Decision Making Self-Efficacy and Career Indecision in Students of SMK Negeri 3 Padang. This type of research is quantitative correlational. The sample of this study was 223 students of SMK Negeri 3 Padang. The data collection method is the Career Decision Making Self-Efficacy and Career Indecision scales which are analyzed by Pearson's correlation test, namely the product moment correlation technique. Based on the results of the hypothesis test, the value of r = -0.326 and the value of p = 0.000 are obtained, indicating that there is a significant negative relationship between Career Decision Making Self-Efficacy and Career Indecision in Students of SMK Negeri 3 Padang.